Reproductive Health Freedom and Domestic Violence in A Patriarchal Society: Some Findings in Akwa Ibom State, Nigeria - Brown, Aniekan S.; Usoro, Nsidibe A. (EDUPEDIA Publisher, 2023)
There is paucity of freedom in the area of reproductive health in patriachal communities which leads to domestic violence. This study looked at the socio-cutural factors and other perculiarities of reproductive health freedom and domestic violence in Ibibioland, South-South Nigeria. With feminism as the theoretical drift, the study utilized interviews and other qualitative methods to elicit data from participants recruited through a multi-staged sampling technique. Simple percentage was the instrument for presentation of socio-demographic statistics of study participants. Emerging data from the largely qualitative work shows that issues of reproductive health freedom and domestic violence mainly border on social power relations against the female gender and cultural worldviews. Since the situation is culturally constructed, the study argues that legal framing and international declarations should be domesticated with vigour. This should be with a view to criminalizing counters to such laws and declartions.